Assessing the Effectiveness of Responsibility Accounting in Enhancing Managerial Accountability and Control - Triyono Triyono (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study examines the effectiveness of responsibility accounting in enhancing managerial accountability and organizational control. Many organizations face challenges in clearly defining managerial responsibilities, monitoring performance, and enforcing control mechanisms, which can lead to inefficiencies and misaligned decision-making. The research aims to assess how structured responsibility accounting systems influence managerial behavior, accountability, and operational oversight. A literature-based methodology was employed, utilizing primary data from relevant case studies and secondary data from books, journals, articles, and organizational reports. Data were analyzed through content analysis to identify patterns, relationships, and insights regarding responsibility allocation, performance measurement, and control practices. The findings indicate that responsibility accounting improves clarity of roles, promotes transparency, supports proactive decision-making, and aligns individual performance with strategic objectives. Despite implementation challenges, it serves as an effective tool for strengthening managerial accountability, optimizing resource utilization, and reinforcing organizational control, providing both practical and theoretical value for contemporary management.